Research on Difficulty in Indonesia Students Learning Chinese Language - Anggreani, Lydia (Bina Nusantara University, 2013)
Chinese has become the worldâ€™s second language. Each language has its own law, as is the Chinese. Indonesian students have difficulty in learning Chinese which are are not surprising. Every language has various characteristics, so do Chinese and Bahasa Indonesia. Article analyzes difficulties to learn Chinese, especially for Indonesian students, those are tone, grammar, sounds of â€œer huaâ€ such as Alice retroflex. The respondents are 100 Indonesian students who are randomly selected for testing samples analyzed. Since there is no tone in Bahasa Indonesia, it makes a lot of Indonesian students in the learning process often appear in Chinese foreign accent phenomenon. This article expects to explore the problem by studying the formation of the causes and solutions. Indonesian students learning Chinese was designed to provide some teaching and learning strategies.